Teach yourself visually Word 2010 - Marmel, Elaine J. (Indianapolis, IN : Wiley, 2010)
Clear, step-by-step screen shots show you how to tackle more than 160 Word 2010 tasks. Each task-based spread covers a single technique, sure to help you get up and running on Word 2010 in no time.
Getting familiar with Word -- Managing documents -- Editing text -- Proofreading in Word -- Formatting text -- Formatting paragraphs -- Formatting pages -- Printing documents -- Creating tables and charts -- Working with graphics -- Customizing Word -- Work with mass mailing tools -- Using Word to interact over the Internet.
Includes index.
Keywords: Microsoft Word; Word processing